The role of electronic health record developers in hospital patient sharing. (6th December 2021) - Pylypchuk, Yuriy; Meyerhoefer, Chad D; Encinosa, William; Searcy, Talisha
Abstract: Objective: To determine whether hospital adoption of a new electronic health record (EHR) developer increases patient sharing with hospitals using the same developer. Materials and Methods: We extracted data on patients shared with other hospitals for 3076 US nonfederal acute care hospitals from the 2011 to 2016 Centers for Medicare & Medicaid Services Physician Shared Patient Patterns database. We calculated the ratio of patients shared with hospitals outside of the focal hospital's network that use the same EHR developer as the focal hospital, and estimated difference-in-differences models to compare same-developer patient sharing among hospitals that switched to a new developer with those that did not switch developer. Results: Switching to a new EHR developer increased the ratio of patients shared with other hospitals having the same EHR developer by 4.1–19.3%, depending on model specification. The magnitude of this effect varied by EHR developer and was increasing in developer market share. Discussion: Consolidation in the EHR industry has led to higher patient sharing among hospitals with the same EHR developer. Contributing factors could include the growth of developer-based health information exchanges, customizable referral management systems, and provider preferences for easy and reliable data exchange. However, hospital transfers that are significantly influenced by EHR developer could lead to poor patient-provider matches. Conclusion: Hospitals' choice of EHR developer impacts the flow of patients across hospitals, which could have both desirable and undesirable effects on patient care. Future research should investigate whether health outcomes decline with greater same-developer patient sharing.